Nanoparticles for improving biogas production and effluent biofertilizer - Taha Abdelfattah Mohammed Abdelwahab; Junting Pan; Ji-Qin Ni; Chunping Yang; Mahendra Kumar Mohanty; Elwan Ali Darwish; Samir Hafez Mohamed Desoky; Haiping Yang; Ahmed Elsayed Mahmoud Fodah (Scientific Reports)
Abstract The impact of nanoparticles (NP) mixtures (Fe + Ni + Co, Fe + Ni, Fe + Co, and Ni + Co) on the anaerobic digestion (AD) of cow manure was examined through kinetic modelling (Modified Gompertz, Logistic, and First-order kinetic) and experimental observations. The NPs mixture significantly enhanced biogas production rate and yield potential. The variation between predicted and actual biogas yields was smaller with the Modified Gompertz model (1.37% to 5.30%) and First-order kinetic model (0.04% to 3.83%) compared to the Logistic model (1.99% to 7.04%). Additionally, digestates containing NPs showed strong fertility properties (5.16% to 5.36%). The combined use of kinetic models and experiments offers an effective way to quantify the influence of NPs mixture on AD performance, aiding in industrial application.